Comparison of laparoscopic verse open oesophagogastric devascularisation with splenectomy in portal hypertension: A meta-analysis - Hu Zhang (Journal of Minimal Access Surgery)
To assess the efficacy and safety in treating portal hypertension by laparoscopic oesophagogastric devascularisation with splenectomy. I searched the randomised controlled trials about the efficacy and safety of laparoscopic oesophagogastric devascularisation with splenectomy in treating portal hypertension from PubMed (1998~2023.02), Wanfang Data (1990~2023.02), China National Knowledge Infrastructure (1979~2023.02), Whip (1989~2023.02) and International Statistical Institute (1998~2023.02). I extracted the data from these trials, and I got the meta-analysis from RevMan 5.3 software. Seventeen randomised control trials involving 1326 patients were included (671 patients in the laparoscopic oesophagogastric devascularisation with splenectomy in the portal hypertension group and 655 patients in the open resection group). Compared with open resection group, this Meta-analysis showed that laparoscopic esophagogastric devascularization with splenectomy in portal hypertension group could reduce the intraoperative bloodloss (P < 0.05), shorten the postoperative time of recovery of intestinal peristalsis (P < 0.05), reduce the postoperative drainage volume (P < 0.05), reduce the drainage tube removal time (P < 0.05), shorten the postoperation hospital stay (P < 0.05), shorten the total hospitalization cost (P = 0.05), shorten the postoperative ambulation (P < 0.05), shorten the postoperative complication rate (P < 0.05). But there was no significant difference in the operation time (P > 0.05). However, there was no significant difference in the operation time (P > 0.05). Compared with open resection group, the total effect of laparoscopic oesophagogastric devascularisation with splenectomy in the treatment of portal hypertension is better. Laparoscopic oesophagogastric devascularisation with splenectomy in the treatment of portal hypertension is acceptable.